Filter Air Untuk Revitalisasi Sumur Artesis Di Dusun III Kelambir Desa Kelambir Pantai Labu - Hestukoro, Soni; Naibaho, Penteris R. P.; Razak, Abdul; Saragi, Jandri Fan HT (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
One of the basic needs for humans is the availability of clean water that can be used for bathing, washing and also consumption. Sources of clean water can be obtained from dug wells, drilled wells, artesian wells, PDAMs and mountain springs. Artesian wells tap water in a confined aquifer layer which is limited by an insulating layer which naturally functions to maintain hydrostatic pressure and limit it to the free aquifer, where in this layer the influence of contamination is less. Kelambir Village has 4 artesian wells that are 30 years old spread across several hamlets, one of which is in hamlet III, Kelambir Village. People are free to use it for various purposes such as cooking, washing and bathing. The artesian well in Kelambir III hamlet was used as a model by the village head to provide clean water for residents by building a water reservoir tower measuring 2x2x2 and a height of 7 m above ground level to be able to channel water to the furthest places more than 3 km away. The characteristics of water from artesian wells are still slightly poor, characterized by changes in color and the presence of sediment. For this reason, the implementation team offers a solution in the form of providing a water filter installation to obtain water that is good quality and suitable for consumption. The water quality obtained after carrying out this activity was much better than the water samples obtained previously.